Length-weight relationships of six syngnathid species from Ria Formosa, SW Iberian coast - Vieira, RP (2016)
In this study, the length-weight (LWR) parameters were estimated for six syngnathid species, including 2 seahorses and 4 pipefishes, from Ria Formosa, a temperate lagoon from the south coast of Portugal. A total of 5070 fishes were used to determine the LWR. The estimated b value ranged from 2.95 (Nerophis ophidion) to 3.36 (Syngnathus abaster). To the authors' best knowledge, LWR parameters were estimated for the first time for Nerophis ophidion and Syngnathus typhle for the Atlantic waters. Data here present are essential for management and conservation of these flagship species.